Resíduos e sombreamento: facilitadores do processo de recuperação de área impactada pela construção da Usina Hidrelétrica de Ilha Solteira - Rigolin, Isabela Marega [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Processes of development in society can be highly impactful on the environment; one example was the process of energy expansion in the 1960s and 1970s. Framework of development in the northwestern region of the state of São Paulo, the construction of the Ilha Solteira hydroelectric plant to provide advances in the region, however its construction brought various environmental impacts, mainly for the soil. The overall objective was to promote the improvement of the re-establishment of native vegetation and the cultivation conditions of the soil through the use of organic waste and the assessment of the contribution of waste in the chemical conditioning of degraded soil and in the establishments of Stylosanthes capitata. The work was divided into two stages: one carried out in a controlled environment (greenhouse) and the second stage in the field. In the first stage, the experiment was conducted in a protected cultivation condition, in an entirely randomized experimental delineation, in a 4 x 4 x 2 factor scheme, with 3 repetitions per treatment and 2 plants per repetition (each plant pot with 10kg soil). The waste, aquatic macrophytes (MAC), and sewage sludge (LOD) were added to the soil in doses of 0, 10, 20, and 30 t ha-1. Sugarcane bagasse ash (CZA) was incorporated into the soil in doses of 0 and 20 t t ha-1, ten days before LOD, MAC, and S. capitata seeds. After 120 days of sowing, the soil was analyzed for fertility and the plants for height, fresh and dry mass of the air, root system, and root volume. The CZA, LOD, and MAC residues raised pH, organic matter, phosphorus, and calcium content, facilitating the establishment of the plant, especially for the dose of 20 t ha-1/ha for LOD and MAC. Thus, it can be recommended to use these residues as both chemical soil conditioners and facilitators in the establishment of S. capitata. The second stage was conducted in field conditions at the Farm of Education, Research, and Extension (FEPE). The experimental area was harrowed once and scarified twice to break the existing sealing on the surface and turn the soil material to a depth of 0.40 m. There were established in the field 36 plots of 25 m2, which received 8 treatments with 4 repetitions, following the experimental model in entirely casualized blocks. The treatments consisted of two organic residues (LOD and CZA) applied in 2 doses (0 and 20 t/ha) and a mix of seeds containing 13 species native to Cerrado, seeds of Stylosanthes spp. cv. Campo Grande (Stylosanthes capitata and Stylosanthes macrocephala) and branches were distributed to the surface to perform shading. Also demarcated in the field were 4 plots that were only mechanized (MEC) and 4 other plots that were preserved without any change (SMEC) for the conduct of comparative evaluations. After sowing, the experimental area began to be irrigated manually twice a week during the months of October and November. Soil temperature assessments were carried out monthly, over the course of thirteen months of conducting the experiment, and measured at a depth of 0.05 m, with three repetitions per plot between 11 and 13 h. The soil moisture assessment was carried out by the gravimetric method and was performed in two stages, at depths of 0 – 0,10; 0,10 – 0,20 and 0,20 – 0,40 m, with two repetitions per plot. The soil samples were collected at a depth of 0 - 0,10 m in two stages for assessments of the following parameters: P, MO, K+, Ca2+, Mg2+, H+Al, Al3+, S-SO4, B, Cu, Fe, Mn, and Zn. The evaluation of spontaneous vegetation was done through the identification of the individuals present in the experimental parcels through the conduct of a census. The assessment of the stylosanthes was done through the visual quality index method performed by two evaluators. The samples of soil penetration resistance, speed of infiltration, and density were collected in two periods. For soil density, macro- and microporosity were determined, as was total porosity. The electronic microscopy was evaluated in order to evaluate the soil morphology. The evaluation of the data was done by means of variance analysis and an average test. Regarding the results, the presence of CZA and LOD had statistically significant effects on plant covering. The presence of LOD raised soil moisture levels in the presence of 20 t ha-1. For the temperature parameter, the presence of shading together with the residues provided a decrease of 3°C in soil temperature. In terms of soil fertility, the elements P, K, Mg, H+Al, Al3+, S-SO4, B, pH, MO, and CTC showed a significant response in the presence of CZA and LOD and in the absence of shadowing. It was also noted that of the 13 species introduced into the experimental area by means of seeds, 9 germinated and survived throughout the first year of cultivation until the evaluation, and 41 spontaneous species emerged, distributed in 13 families, the Fabaceae and Poaceae Families being highlighted. Already in the soil density parameter, lower content was noted in the mechanized areas since they did not receive any treatment. The soil that was not mechanization presented higher values of resistance to penetration, and the data from electronic microscopy pointed to the presence of biocrusts in the evaluated parcels. In the treatments with the realization of mechanization, they were found fragmented. After evaluations, it is considered that mechanization reduced the mechanical resistance to soil penetration, soil density showed a decrease in the areas with mechanization, and the addition of CZA, LOD, and shading favored the emergence of 41 species in the total area.

Processes of development in society can be highly impactful on the environment; one example was the process of energy expansion in the 1960s and 1970s. Framework of development in the northwestern region of the state of São Paulo, the construction of the Ilha Solteira hydroelectric plant to provide advances in the region, however its construction brought various environmental impacts, mainly for the soil. The overall objective was to promote the improvement of the reestablishment of native vegetation and the cultivation conditions of the soil through the use of organic waste and the assessment of the contribution of waste in the chemical conditioning of degraded soil and in the establishments of Stylosanthes capitata. The work was divided into two stages: one carried out in a controlled environment (greenhouse) and the second stage in the field. In the first stage, the experiment was conducted in a protected cultivation condition, in an entirely randomized experimental delineation, in a 4 x 4 x 2 factor scheme, with 3 repetitions per treatment and 2 plants per repetition (each plant pot with 10kg soil). The waste, aquatic macrophytes (MAC), and sewage sludge (LOD) were added to the soil in doses of 0, 10, 20, and 30 t ha-1 . Sugarcane bagasse ash (CZA) was incorporated into the soil in doses of 0 and 20 t t ha-1 , ten days before LOD, MAC, and S. capitata seeds. After 120 days of sowing, the soil was analyzed for fertility and the plants for height, fresh and dry mass of the air, root system, and root volume. The CZA, LOD, and MAC residues raised pH, organic matter, phosphorus, and calcium content, facilitating the establishment of the plant, especially for the dose of 20 t ha-1 /ha for LOD and MAC. Thus, it can be recommended to use these residues as both chemical soil conditioners and facilitators in the establishment of S. capitata. The second stage was conducted in field conditions at the Farm of Education, Research, and Extension (FEPE). The experimental area was harrowed once and scarified twice to break the existing sealing on the surface and turn the soil material to a depth of 0.40 m. There were established in the field 36 plots of 25 m2, which received 8 treatments with 4 repetitions, following the experimental model in entirely casualized blocks. The treatments consisted of two organic residues (LOD and CZA) applied in 2 doses (0 and 20 t/ha) and a mix of seeds containing 13 species native to Cerrado, seeds of Stylosanthes spp. cv. Campo Grande (Stylosanthes capitata and Stylosanthes macrocephala) and branches were distributed to the surface to perform shading. Also demarcated in the field were 4 plots that were only mechanized (MEC) and 4 other plots that were preserved without any change (SMEC) for the conduct of comparative evaluations. After sowing, the experimental area began to be irrigated manually twice a week during the months of October and November. Soil temperature assessments were carried out monthly, over the course of thirteen months of conducting the experiment, and measured at a depth of 0.05 m, with three repetitions per plot between 11 and 13 h. The soil moisture assessment was carried out by the gravimetric method and was performed in two stages, at depths of 0 – 0,10; 0,10 – 0,20 and 0,20 – 0,40 m, with two repetitions per plot. The soil samples were collected at a depth of 0 - 0,10 m in two stages for assessments of the following parameters: P, MO, K+ , Ca2+, Mg2+, H+Al, Al3+, S-SO4, B, Cu, Fe, Mn, and Zn. The evaluation of spontaneous vegetation was done through the identification of the individuals present in the experimental parcels through the conduct of a census. The assessment of the stylosanthes was done through the visual quality index method performed by two evaluators. The samples of soil penetration resistance, speed of infiltration, and density were collected in two periods. For soil density, macro- and microporosity were determined, as was total porosity. The electronic microscopy was evaluated in order to evaluate the soil morphology. The evaluation of the data was done by means of variance analysis and an average test. Regarding the results, the presence of CZA and LOD had statistically significant effects on plant covering. The presence of LOD raised soil moisture levels in the presence of 20 t ha-1 . For the temperature parameter, the presence of shading together with the residues provided a decrease of 3°C in soil temperature. In terms of soil fertility, the elements P, K, Mg, H+Al, Al3+, S-SO4, B, pH, MO, and CTC showed a significant response in the presence of CZA and LOD and in the absence of shadowing. It was also noted that of the 13 species introduced into the experimental area by means of seeds, 9 germinated and survived throughout the first year of cultivation until the evaluation, and 41 spontaneous species emerged, distributed in 13 families, the Fabaceae and Poaceae Families being highlighted. Already in the soil density parameter, lower content was noted in the mechanized areas since they did not receive any treatment. The soil that was not mechanization presented higher values of resistance to penetration, and the data from electronic microscopy pointed to the presence of biocrusts in the evaluated parcels. In the treatments with the realization of mechanization, they were found fragmented. After evaluations, it is considered that mechanization reduced the mechanical resistance to soil penetration, soil density showed a decrease in the areas with mechanization, and the addition of CZA, LOD, and shading favored the emergence of 41 species in the total area.
Waste and shadowing: facilitators of the recovery process of area impacted by the construction of the Ilha Solteira hydroelectric plant
Keywords: Impactos ambientais; Degradação do solo; Resíduos orgânicos; Vegetação espontânea; Environmental impacts; Soil degradation; Organic waste; Spontaneous vegetation